2019
DOI: 10.2147/cmar.s214243
|View full text |Cite
|
Sign up to set email alerts
|

<p>Overexpressed PKMYT1 promotes tumor progression and associates with poor survival in esophageal squamous cell carcinoma</p>

Abstract: BackgroundEsophageal squamous cell carcinoma (ESCC) is one of the most common malignant tumors worldwide and the 5-year overall survival rate remains poor. Protein kinase, membrane associated tyrosine/threonine (PKMYT1) is overexpressed in several cancers and participate in tumor progression. However, the mechanism of PKMYT1 in ESCC is unclear.PurposeThe objective of our study was to demonstrate the the expression and role of PKMYT1 in ESCC.Patients and methods  We detected the expression of PKMYT1 in ESCC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 51 publications
(62 reference statements)
5
22
0
Order By: Relevance
“…Consistent with the present results, PKMYT1 has been shown to be upregulated in oncogenesis and progression of multiple human tumors, including colorectal cancer [ 49 ], esophageal squamous cell carcinoma (ESCC) [ 11 ], hepatocellular carcinoma (HCC) [ 22 ], non-small-cell lung cancer (NSCLC) [ 24 ], gastric cancer (GC) [ 21 ], and breast cancer [ 13 ], as well as OC [ 23 ]. These reports have also revealed a significant correlation between increased PKMYT1 expression and advanced clinical stage and progressive histological grade, as well as unsatisfactory prognosis of diversiform tumors [ 11 , 13 , 21 – 24 , 49 ], which coincides with the results from our study. One report revealed that mutation in the C-terminal domain of PKMYT1 influenced the prognosis of neuroblastoma by altering its catalytic activity [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with the present results, PKMYT1 has been shown to be upregulated in oncogenesis and progression of multiple human tumors, including colorectal cancer [ 49 ], esophageal squamous cell carcinoma (ESCC) [ 11 ], hepatocellular carcinoma (HCC) [ 22 ], non-small-cell lung cancer (NSCLC) [ 24 ], gastric cancer (GC) [ 21 ], and breast cancer [ 13 ], as well as OC [ 23 ]. These reports have also revealed a significant correlation between increased PKMYT1 expression and advanced clinical stage and progressive histological grade, as well as unsatisfactory prognosis of diversiform tumors [ 11 , 13 , 21 – 24 , 49 ], which coincides with the results from our study. One report revealed that mutation in the C-terminal domain of PKMYT1 influenced the prognosis of neuroblastoma by altering its catalytic activity [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…Another report revealed that depletion of PKMYT1 suppressed the β-catenin/TCF pathway, which is considered a driver of the EMT in multiple tumors and that the gene can interact with primary EMT-related biomarkers, such as Twist, Snail, and Slug [ 22 , 52 , 53 ]. Similarly, downregulation of PKMYT1 impeded Twist expression by hindering the Akt/mTOR pathway, thus suppressing migration and metastasis as well the EMT process in ESCC cells [ 11 ]. Considering that EMT is a crucial determinant for tumor metastasis and progression [ 52 , 53 ], targeting the β-catenin/TCF and Akt/mTOR pathway through PKMYT1 may be a promising strategy for tumor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…22 Other studies have detected differential expression of PKMYT1 in lung, esophageal, and colorectal cancers. [23][24][25] In this study, we first confirmed that PKMYT1 was upregulated in GC tissues and that high expression of PKMYT1 was an independent risk factor for poor prognosis in patients with GC. In terms of cell function, we found that the knockdown of PKMYT1 affected the GC cell cycle, inhibited the proliferation ability GC cells, and promoted GC cell apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…In neuroblastic tumors, PKMYT1 is required to stabilize MYCN protein, which is a crucial proto-oncogene for this cancer types [ 52 ]. Moreover, in esophageal squamous cell carcinoma (ESCC) cell lines and primary cells, the expression of PKMYT1 is associated with and regulates the activation of the AKY/mTOR pathway [ 53 ] (Table 1 ). Taken together, this evidence suggests a broad role of WEE1/PKMYT1 besides the DNA damage response pathway that may increase the interest towards its therapeutic targeting.…”
Section: Wee1 and Pkmyt1 Deregulation In Cancer Cellsmentioning
confidence: 99%